2017
DOI: 10.3389/fmicb.2017.01330
|View full text |Cite
|
Sign up to set email alerts
|

Legionella Persistence in Manufactured Water Systems: Pasteurization Potentially Selecting for Thermal Tolerance

Abstract: Legionella is an opportunistic waterborne pathogen of increasing public health significance. Pasteurization, otherwise known as super-heat and flush (increasing water temperature to above 70°C and flushing all outlets), has been identified as an important mechanism for the disinfection of Legionella in manufactured water systems. However, several studies have reported that this procedure was ineffective at remediating water distribution systems as Legionella was able to maintain long term persistent contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 60 publications
(78 reference statements)
1
35
0
Order By: Relevance
“…counts and the decrease and increase of temperature in hot and cold water samples, respectively. A strong correlation between Legionella pneumophila strains and high temperature values have also been observed in further studies [ 22 ], which highlights how pasteurization methods may disinfect the waters, but it may influence the persistence of thermo-tolerant Legionella pneumophila bacteria in viable, but non cultivable (VBNC) forms.…”
Section: Discussionmentioning
confidence: 57%
“…counts and the decrease and increase of temperature in hot and cold water samples, respectively. A strong correlation between Legionella pneumophila strains and high temperature values have also been observed in further studies [ 22 ], which highlights how pasteurization methods may disinfect the waters, but it may influence the persistence of thermo-tolerant Legionella pneumophila bacteria in viable, but non cultivable (VBNC) forms.…”
Section: Discussionmentioning
confidence: 57%
“…For such conditions to take place, a series of variables must co-occur, such as the increased temperature of cold water or decreased temperature of hot water (optimally 35–46 °C), absence of water disinfectants or under-treated water, out of range pH values (5.5–9.2), presence of substances like iron salts and l -cysteine, as well as, co-existing and supporting microbial flora. Furthermore, other factors such as the complexity of the architecture of the pipe system (high surface to volume ratio), presence of blunt-end pipes, infrequently used pipe terminals, pipelines exposed to the sun heat, close proximity of hot and cold-water pipelines, insufficient maintenance and end-points creating aerosols, have all been evaluated to significantly affect the rate and extent of Legionella colonization in water systems [ 27 ]. All these factors may well be associated with the formation of biofilms, which can provide a means for the survival and dissemination of the pathogen and undermine the efforts to eradicate bacteria from water systems [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the presence of L. pneumophila in disinfected water supplies [60,61]. An important factor enabling L. pneumophila survival in the built environment is its interaction with a protozoan host [62][63][64] (as mentioned in Table 3).…”
Section: Implications For the Control Of L Pneumophilamentioning
confidence: 99%